Long-term outcomes following recovery from severe primary graft dysfunction after heart transplantation - Hunteria Nelson, Rubyen Patrick; Feng, Iris; Vinogradsky, Alice V; Barile, Joseph; Wang, Chunhui; Zhao, Yanling; Latif, Farhana; Sayer, Gabriel T; Uriel, Nir Y; Naka, Yoshifumi; Kurlansky, Paul; Takeda, Koji (The Journal of thoracic and cardiovascular surgery, 2025)
To investigate long-term outcomes of orthotopic heart transplantation (OHT) recipients after recovery from severe primary graft dysfunction (PGD), a major risk factor for early mortality after OHT. This single-center retrospective study included 417 adult patients who underwent isolated primary OHT at our center between 2015 and 2022. During this study period, our center applied a protocolized approach using extracorporeal membrane oxygenation (ECMO) to treat all patients who developed severe PGD. Patients were thus divided into 2 cohorts: those requiring ECMO for severe PGD (PGD-ECMO) and all others (non-PGD). The primary outcome of this study was long-term survival. Secondary outcomes included adverse events, readmissions, and graft function by echocardiography. Propensity score matching (PSM) and multivariable Cox regression were used to balance baseline differences between cohorts. Fifty-four (12.9%) OHT recipients required ECMO for severe PGD during the study period. After PSM, there were no significant differences in baseline characteristics between cohorts. Survival to discharge without retransplantation was significantly lower in the PGD-ECMO group (88.9% vs 100%; P = .009), and retransplantation was rare overall. However, multivariable Cox-adjusted analysis of PSM cohorts demonstrated no significant difference in 8-year survival from time of discharge (hazard ratio, 1.043; 95% confidence interval, 0.446-2.441; P = .923). Echocardiographic analysis showed similar biventricular function and valve competence in the 2 cohorts at various time points up to 2 years post-transplantation, as well as an equivalent cumulative incidence of readmission. This study demonstrates that patients with severe PGD requiring ECMO support can achieve equivalent long-term outcomes as their non-PGD counterparts if they recover during the index hospitalization. This finding highlights the importance of the perioperative period after OHT and prompt treatment of severe PGD.